Modern philosophy - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Films for the Humanities & Sciences, 2004)
In this program, Paul Guyer, of the University of Pennsylvania; Rutgers University's Colin McGinn; and Princeton University's Kwame Anthony Appiah and Daniel Garber address the major philosophical currents of that era and the explosive controversies surrounding them. Bacon's Novum Organum, Descartes's 2Discourse on the Method,3 Hobbes' Leviathan, Spinoza's Ethics, and other germane works are cited
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
Narrator: Liz Chang, Juan Antonio Middleton
DVD format
Keywords: Philosophy; Philosophy, Renaissance; Philosophy, European